SIFAT PEMESINAN LIMA JENIS KAYU DOLOK DIAMETER KECIL DARI JAMBI - Jamaludin Malik; Osly Racbman (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
This paper deals with a study in machining properties of small diameter log of five wood species, i.e. mahang (Macaranga pruinosa Muell. Arg.), medang kuning (Litsea sp.), bayur (Pterospermum diversifolium Bl.), balam merah (Palaquium gutta Baill.), and merkubung (Macaranga gigantea Muell. Arg) using LPHH (1976) Standard and modified ASTM D 1666-64.The results revealed that in planing aspect, mahang, medang, balam, and merkubung belonged to class I (very good); Bayur to class II (good). In shaping aspect. mahang and balam belonged lo class 1, bayur and merkubung to class II. and medang to class Ill (moderate). In turning aspect, balam belonged to class I and mahang lo class V; medang, bayur and merkubung lo class II. In boring aspects, medang and bayur belonged to class II; balam to class III; mahang and merkubung to class IV (poor). In sanding aspect all wood species belonged to class I. All these wood species may be suitable for furniture and other secondary industry.